Nursing Period, Behavior Development, and Growth Pattern of a Newborn Formosan Pangolin (Manis pentadactyla pentadactyla) in the Wild - Sun, Nick Ching-Min; Jephte Sompud; Pei, Kurtis Jai-Chyi (SAGE Publications Inc, 2018)
The Formosan pangolin mainly inhabits the lowland forest in Taiwan. Biological information on pangolins is limited due to their solitary behavior. This study reports the first field record of the behavior development and growth pattern of a newborn male Formosan pangolin during the entire nursing period in the wild. The methods used in this study were radio-tagging and camera-trapping. Data collection for this study was conducted from November 2014 until May 2015. The nursing period was 157 days. The infant started to exit the nursing burrow alone at 11 weeks old, with significant soil scraping and licking behaviors. The duration and distance of the exploring were both extended considerably after 15 weeks old. All exploring behaviors that were recorded occurred after the mother had left the burrow. The total body length of the infant pangolin growth was at a relative constant rate of 1.2 cm/week during the nursing period, which was faster than the only record from a hand-reared individual (0.7 cm/week). This study presents a useful method to monitor the maternal behaviors and infant growth pattern for the Formosan pangolin under natural conditions.